Four-quadrant control of multilevel inverter fed induction motor drives - Dandil, Besir; Tuncer, Servet (Natl Inst Science Communication-Niscair, 2008)
This paper presents a high performance speed and current control scheme based on indirect field oriented control (IFOC) for multilevel inverter fed induction motor drive. Advantages of multilevel inverters over standard two-level voltage source inverter (VSI) include a greater number of levels in output voltage waveforms, less harmonic distortion in voltage and current waveforms and lower switching frequency. Proposed IFOC scheme of multilevel inverter showed high quality of control.
Keywords: indirect field oriented control (IFOC); induction motor; multilevel inverter; sinusoidal pulse width modulation